Frequency of chromosomal aneuploidy in high quality embryos from young couples using preimplantation genetic screening - Farzaneh Fesahat; Fatemeh Montazeri; Mohammad Hasan Sheikhha; Hojjatollah Saeedi; Razieh Dehghani Firouzabadi; Seyed Mehdi Kalantar (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Selection of the best embryo for transfer is very important in assisted reproductive technology (ART). Using morphological assessment for this selection demonstrated that the correlation between embryo morphology and implantation potential is relatively weak. On the other hand, aneuploidy is a key genetic factor that can influence human reproductive success in ART. Objective: The aim of this lab trial study was to evaluate the incidence of aneuploidies in five chromosomes in the morphologically high-quality embryos from young patients undergoing ART for sex selection. Materials and Methods: A total of 97 high quality embryos from 23 women at the age of 37or younger years that had previously undergone preimplantation genetic screening for sex selection were included in this study. After washing, the slides of blastomeres from embryos of patients were reanalyzed by fluorescence in-situ hybridization for chromosomes 13, 18 and 21. Results: There was a significant rate of aneuploidy determination in the embryos using preimplantation genetic screening for both sex and three evaluated autosomal chromosomes compared to preimplantation genetic screening for only sex chromosomes (62.9% vs. 24.7%, p=0.000). The most frequent detected chromosomal aneuploidy was trisomy or monosomy of chromosome 13. Conclusion: There is considerable numbers of chromosomal abnormalities in embryos generated in vitro which cause in vitro fertilization failure and it seems that morphological characterization of embryos is not a suitable method for choosing the embryos without these abnormalities